A CD1c lipid agnostic T cell receptor bispecific engager redirects T cells against CD1c+ cells - Szoke-Kovacs, Rita; Khakoo, Sophie; Rangel, Victor Lopes; Della Cristina, Pietro; Pentier, Johanne; Khanolkar, Rahul; El-Ajouz, Sam; Simmons, Robert; Cole, David K.; Gogolak, Peter; Salio, Mariolina; Karuppiah, Vijaykumar (Frontiers in Immunology, 2025)
IntroductionImmunotherapy is emerging as an efficacious treatment for some cancers, complementing traditional chemo-radiation therapies. Specific markers at the cell surface of cancer cells can be used as immunotherapy targets. However, many of these markers are defined by a patient’s genetic background, limiting their use across the human population.MethodsHere, we investigated the non-polymorphic antigen presenting molecule, CD1c, that is only expressed on subsets of mature hematopoietic cells, as a potential immunotherapy target with reduced risk of off-tumor on-target toxicity in healthy tissues.Results and discussionWe identified a T cell receptor (TCR) which recognises CD1c in a lipid independent manner and determined the crystal structure of the TCR-CD1c complex which revealed flexibility around the lipid binding region, and a new binding mechanism of auto-antigen recognition. We generated affinity enhanced variants of the TCR and fused them to an anti-CD3 antibody for T cell redirection. Lipidomic analysis revealed promiscuous lipid recognition of CD1c by the affinity enhanced TCR variants, with preference for larger lipid head group, a finding which is supported by the crystal structure. The bispecific molecule induced potent re-directed T cell killing of CD1c positive cell lines. These proof-of-concept findings demonstrate that CD1c targeting TCR bispecific engagers might be good candidates for the development of non-MHC restricted, universal therapeutics for the treatment of CD1c+ leukemias.